A little healthy competition: using mixed methods to pilot a team-based digital game for boosting medical student engagement with anatomy and histology content. Issue 1 (December 2015) - Janssen, Anna; Shaw, Tim; Goodyear, Peter; Kerfoot, B.; Bryce, Deborah
Abstract Background Digital games have been demonstrated to be beneficial for a range of non-recreational purposes, with a particular focus on their value for education. There is a limited amount of research supporting their use for medical education, but their are several studies on their use in areas such as surgical training, and life-support re-training. However, a significant gap exists in demonstrating how they engage with learners and games can be used most effectively in medical education. This pilot study assessed the value of digital games for teaching anatomy, by evaluating participant engagement and their attitudes towards a team-based strategy game. Methods A digital game platform was designed, and then populated with anatomy questions developed by subject matter experts. Second year medical students were recruited to play three matches of the game. At the end of each match participants were asked to complete a Likert rating of their experiences of the game across five domains. Semi-structured interviews were conducted to assess engagement with the platform and perceived value to learners. Results Sixteen participants volunteered to participate. Post-match ratings indicated that participants had a generally positive experience with the game, with 89 % of respondents agreeing the game was engaging, 93 % of respondents agreeing the game was challenging and 74 % indicating they would like to play the game again if given the opportunity. A total of fourteen participants agreed to be interviewed after playing three matches of the game. Interview responses supported the findings of the post-match ratings that the game was considered enjoyable and engaging. Participants noted they particularly enjoyed the competitive aspect of the game, particularly the opportunity to play against peers they consider their academic equals. In addition to finding the game engaging interview participants indicated they perceived the game impacted on their knowledge around anatomy. In particular, participants noted that the game provided them unique insight into their knowledge strengths and deficits. Conclusions This study demonstrated that digital games can engage medical students in traditionally-challenging areas such as anatomy and offer learners unique insights into their knowledge strengths and deficits.